Vascular cell adhesion molecule‑1 levels in patients with coronary artery disease with type 2 diabetes mellitus - Serik, S.A.; Mavrycheva, N.R. (Medicni Perspektivi, 2023)
Chronic systemic inflammation is a key component of the pathogenesis of both type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD). Soluble vascular cell adhesion molecule‑1 (sVCAM‑1) is considered as the indicator of vascular inflammation and endothelial activation. The aim of our study was to investigate sVCAM‑1 levels in patients with CAD with T2DM and to determine their dependence on a previous history of myocardial infarction (MI). The study included 52 patients with stable CAD with T2DM, 20 CAD patients without diabetes and 14 control group persons. sVCAM-1 levels were measured in serum by the enzyme-linked immunosorbent assay. sVCAM‑1 levels in patients with CAD with T2DM and patients with CAD without diabetes were higher than in the control group (p<0,001 and p<0,001, respectively). The difference in sVCAM‑1 levels between CAD patients with T2DM and without diabetes was not significant (p=0,355). There were no significant correlations of sVCAM‑1 levels with glucometabolic indices in any group. Only in patients with CAD with T2DM sVCAM‑1 level negatively correlated with high-density lipoprotein cholesterol. CAD patients with and without T2DM with a history of myocardial infarction (MI) had higher sVCAM‑1 levels than patients without previous MI (p=0,038, р=0,043, respectively). Only in diabetic CAD patients sVCAM‑1 levels were increased in those without a history of MI (р=0,036, in comparison with the controls). There were no correlations between sVCAM‑1 levels and left ventricular remodeling indices in patients either with or without MI. Conclusions. In patients with CAD with T2DM and patients with CAD without T2DM, sVCAM‑1 levels increased in comparison with the controls. However, in patients without diabetes sVCAM‑1 level was increased only in those with previous MI. In patients with T2DM, sVCAM‑1 level increased in the absence of previous MI and there was the further significant increase of its level in postinfarction cardiosclerosis.